2018
DOI: 10.1002/ceat.201700398
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behavior of Glycine Molecules with Electrolytic Dissociation on Charged Silica Gel Particles

Abstract: The surface charge of metal oxides in the solution phase may be a driving force for crystallization. Composite particles were prepared using the principle of heterogeneous nucleation on a metal surface with varying charge density. The electrical properties of the silica gel particles in an electrolyte solution were controlled by the pH, and the zero charge point and charge density of the silica gel particles were determined by titration. The morphology of the glycine particles on the silica gel surface depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…[211] The ratio of the concomitant precipitation of α-, β-, γ-polymorphs was changed, and in some cases also phase-pure batches could be obtained. Other widely used techniques of polymorph control of glycine include crystallization in confined media: micro-and nanopores, [116,212,213] emulsions [214][215][216][217][218][219][220] or at the air-liquid interfaces, Langmuir-Blodgett films of resolved α-amino acids [221][222][223][224][225][226] or at the various solid surfaces (graphene, [227] charged silica gel particles, [228] (111)Pt/SiO 2 /Si substrates, [229] including patterned surfaces [230] ). The effect on polymorphism can in these cases be related both to the nucleation and to the growth of nuclei that starts as a two-dimensional oriented growth pre-determined by the structure of the surface of the substrate and its interactions with the glycine and solvent molecules.…”
Section: Crystallization Procedures and Mechanismsmentioning
confidence: 99%
“…[211] The ratio of the concomitant precipitation of α-, β-, γ-polymorphs was changed, and in some cases also phase-pure batches could be obtained. Other widely used techniques of polymorph control of glycine include crystallization in confined media: micro-and nanopores, [116,212,213] emulsions [214][215][216][217][218][219][220] or at the air-liquid interfaces, Langmuir-Blodgett films of resolved α-amino acids [221][222][223][224][225][226] or at the various solid surfaces (graphene, [227] charged silica gel particles, [228] (111)Pt/SiO 2 /Si substrates, [229] including patterned surfaces [230] ). The effect on polymorphism can in these cases be related both to the nucleation and to the growth of nuclei that starts as a two-dimensional oriented growth pre-determined by the structure of the surface of the substrate and its interactions with the glycine and solvent molecules.…”
Section: Crystallization Procedures and Mechanismsmentioning
confidence: 99%
“…Polymorph crystallization regulated with tailor-made additive 15−17 is well known, in which the structurally similar foreign compound is designed for selective binding to specific faces and preferential inhibition of one crystal form, leaving another crystal form to crystallize unhindered. 18,19 Although previous studies suggested that charged species of the glycine molecule may self-inhibit the crystallization of the α polymorph and afford the formation of the γ form under acidic or basic conditions, 20 the capability of self-inhibition by enantiomer solutes has not been reported thus far. Herein, we discovered that the excessive enantiomer in solution self-inhibits preferentially the stable polymorph, which leaves the always crystallization of the metastable form of DL-methionine. DL-methionine (DL-Met) is the only sulfur-containing essential amino acid used as an additive in food and pharmaceuticals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chiral molecular centers or symmetry constraints limit the number of energetically favorable packing arrangements available to chiral molecules; however, the underlying interplay mechanism of molecular self-assembly and chiral recognition on polymorphic crystallization remains elusive. Polymorph crystallization regulated with tailor-made additive is well known, in which the structurally similar foreign compound is designed for selective binding to specific faces and preferential inhibition of one crystal form, leaving another crystal form to crystallize unhindered. , Although previous studies suggested that charged species of the glycine molecule may self-inhibit the crystallization of the α polymorph and afford the formation of the γ form under acidic or basic conditions, the capability of self-inhibition by enantiomer solutes has not been reported thus far. Herein, we discovered that the excessive enantiomer in solution self-inhibits preferentially the stable polymorph, which leaves the always crystallization of the metastable form of dl -methionine.…”
Section: Introductionmentioning
confidence: 99%
“…et al, 2019;Karger-Kocsis J. et al, 2014;Pierpaoli M. et al, 2019). Since powder properties play a key role in the suitability for a particular application (Kimura T. et al, 2020), selecting the optimal combination of particles is crucial for the performance of the composite particles (Deki Y. et al, 2018). For example, composite particles consisting of oxides, such as SiO 2 and TiO 2 , are utilized in cosmetics and ceramics because of their superior physical properties including optical and electrical properties (Adebisi A.A. et al, 2016;Himoto I. et al, 2016).…”
Section: Introductionmentioning
confidence: 99%